Antibacterial Potential of Cinnamomum culilaban Bark Ethanolic Extract Prepared by Ultrasound-Assisted Extraction against Oral Pathogens - Kurniatri, Arifayu Addiena; Elya, Berna; Suryadi, Herman (Jurnal Kefarmasian Indonesia, 2024)
Cinnamomum culilaban is one of the native Indonesian plants that has been used as medicinal plant. The local community on Seram Island uses the stem bark to treat toothaches. Eugenol, a chemical compound found in Cinnamomum culilaban, is used in dental practice and has antibacterial activity. Research on Cinnamomum culilaban is very limited, its activity against bacteria that cause oral infections has not been reported. This study aims to investigate the antibacterial activity of Cinnamomum culilaban bark extract against oral pathogens Porphyromonas gingivalis, Streptpcoccus mutans, and Enterococcus faecalis. The extraction was carried out using 96% ethanol with ultrasound-assisted extraction method. Disc diffusion assay was conducted to investigate the antibacterial activity. The concentration of extract used were 50%, 25%, and 12.5% (b/v) in DMSO. Eugenol (50% v/v in DMSO) was used as positive control. The phytochemicals screening was carried out to investigate the chemical compounds contained in Cinnamomum culilaban bark extract. Extraction of Cinnamomum culilaban bark using 96% ethanol with the ultrasound-assisted extraction method obtained a yield of 23.36±0.49%. The extract contains alkaloids, flavonoids, tannins, saponins, phenolics, and steroids/terpenoids. The ethanolic extract of Cinnamomum culilaban bark has inhibitory activity against Streptpcoccus mutans and Enterococcus faecalis. Cinnamomum culilaban bark has the potential as an antibacterial agent.